2014
DOI: 10.1080/1331677x.2014.952107
|View full text |Cite
|
Sign up to set email alerts
|

CAPM augmented with liquidity and size premium in the Croatian stock market

Abstract: This article examines the following models: Capital Asset Pricing Model (CAPM) (Sharpe, 1964), and Liquidity CAPM (Hearn, Piesse and Strange, 2009) in the Croatian stock market. We used daily data for the period [2005][2006][2007][2008][2009]. The goal of this article is to examine the impact of an overall market factor, factor related to the firm size, and factor of liquidity risk on expected asset returns in the Croatian stock market. We found that Liquidity Capital Asset Pricing Model (LCAPM) model performs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Success of the Fama-French three factor model is, basically, a divergence in CAPM and emerged as a most popular explanation for the ongoing argument on asset pricing. However, several studies in the financial literature (e.g., Groenewold Fraser 1997;Beltratti and Tria 2002;Drew and Veeraraghan 2002;Mirza and Shahid 2008;Guo et al 2008;Lischewski and Voronkova 2012;Cakici et al 2013;Minović and Živković 2014;Baek and Bilson 2015;Boamah 2015;Ceylan et al 2015;Zaremba and Konieczka 2015;Elgammal et al 2016;Chung et al 2016; Xie and Qu 2016; Kubota and Takehara 2017) attribute mixed evidence regarding the existence, significance, augmented versions and time varying behavior of the risk premiums and the three-factor model in the stock markets of USA, Europe, Australia, Asia and Africa by applying various models and portfolio construction methodologies. Daniel and Titman (1997) examined the Fama and French (1993) and demonstrated that size and book-to-market factors are highly correlated with the average stocks returns but there is no separate distress and most of the co-movement of the value stocks is not due to distressed stocks being exposed to a unique distress factor.…”
Section: Prior Related Studiesmentioning
confidence: 99%
“…Success of the Fama-French three factor model is, basically, a divergence in CAPM and emerged as a most popular explanation for the ongoing argument on asset pricing. However, several studies in the financial literature (e.g., Groenewold Fraser 1997;Beltratti and Tria 2002;Drew and Veeraraghan 2002;Mirza and Shahid 2008;Guo et al 2008;Lischewski and Voronkova 2012;Cakici et al 2013;Minović and Živković 2014;Baek and Bilson 2015;Boamah 2015;Ceylan et al 2015;Zaremba and Konieczka 2015;Elgammal et al 2016;Chung et al 2016; Xie and Qu 2016; Kubota and Takehara 2017) attribute mixed evidence regarding the existence, significance, augmented versions and time varying behavior of the risk premiums and the three-factor model in the stock markets of USA, Europe, Australia, Asia and Africa by applying various models and portfolio construction methodologies. Daniel and Titman (1997) examined the Fama and French (1993) and demonstrated that size and book-to-market factors are highly correlated with the average stocks returns but there is no separate distress and most of the co-movement of the value stocks is not due to distressed stocks being exposed to a unique distress factor.…”
Section: Prior Related Studiesmentioning
confidence: 99%
“…It is noticed that the sample and liquidity proxy used determines the preciseness of liquidity risk measurement. Testing standard and Liquidity CAPM (LCAPM) on Croatian stock market for the period from 2005-2009 showed that LCAPM performs better in explaining stock returns than the CAPM [17]. Authors assumed that classical CAPM does not capture liquidity risk that is the key problem on such small and underdeveloped markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Eraslan (2013) tests the validity of the Fama-French three-factor asset pricing model on the Istanbul stock exchange and conclude that the model has modest explanatory power to explain variations in excess portfolio returns. Minović and Živković (2014) use augmented CAPM by including the factor of liquidity and size on the Croatian stock market. Results indicate that liquidity augmented model performs better in explaining stock returns than the standard CAPM.…”
Section: Brief Review Of Empirical Studies In Asset Pricingmentioning
confidence: 99%